Clinical Features and Computed Tomography Findings Are Utilized to Characterize Retrobulbar Disease in Dogs - Winer, Jenna N.; Verstraete, Frank J. M.; Cissell, Derek D.; Le, Catherine; Vapniarsky, Natalia; Good, Kathryn L.; Gutierrez, Claudio J.; Arzi, Boaz (Frontiers in Veterinary Science, 2018)
The objective of this study is to describe the clinical features and computed tomography (CT) findings of dogs with retrobulbar disease. There are two facets to this study: a retrospective case series in which findings of dogs with primary vs. secondary retrobulbar disease are described, and a retrospective cross-sectional study in which computed tomography findings of dogs with retrobulbar neoplasia vs. infection/inflammation are described and compared. The medical records of 66 client-owned dogs diagnosed with retrobulbar disease between 2006 and 2016 were reviewed. Clinical information including signalment, the specialty service to which the dog was presented, clinical signs, physical examination findings, diagnostic results, treatment, and outcome were documented. Diagnostic imaging and histopathology were reviewed. Forty-one dogs (62.1%) were diagnosed with primary disease of the retrobulbar space; 25 dogs (37.9%) were considered to have secondary retrobulbar disease. Of the 41 dogs with primary retrobulbar disease, 19 were diagnosed with neoplasia, 19 with infectious/inflammatory disease, and 3 suffered traumatic insult to the retrobulbar space. Of the 25 dogs with secondary retrobulbar disease, 21 were diagnosed with neoplasia, 3 with infectious/inflammatory disease, and 1 with a cyst. Dogs had a combination of ocular, oral, and/or nasal clinical signs. CT findings of orbital osteolysis, orbital periosteal reaction, and presence of a retrobulbar mass were significantly associated with neoplasia, while zygomatic salivary gland enlargement, retrobulbar mass effect, and mandibular lymphadenopathy were more often associated with infectious/inflammatory disease. CT findings overlap among different retrobulbar diseases, but new bone formation and lysis are more often associated with neoplasia. Disease originating from the retrobulbar space was equally likely to be infectious/inflammatory (n = 19) or neoplastic (n = 19), based on definitive diagnostic results of dogs with primary retrobulbar disease. Due to the clinical ramifications of these disorders, the diagnosis and treatment of these cases should be managed with a multi-specialty approach.